2016
DOI: 10.1038/srep36909
|View full text |Cite
|
Sign up to set email alerts
|

Mitsugumin 53 regulates extracellular Ca2+ entry and intracellular Ca2+ release via Orai1 and RyR1 in skeletal muscle

Abstract: Mitsugumin 53 (MG53) participates in the membrane repair of various cells, and skeletal muscle is the major tissue that expresses MG53. Except for the regulatory effects of MG53 on SERCA1a, the role(s) of MG53 in the unique functions of skeletal muscle such as muscle contraction have not been well examined. Here, a new MG53-interacting protein, Orai1, is identified in skeletal muscle. To examine the functional relevance of the MG53-Orai1 interaction, MG53 was over-expressed in mouse primary or C2C12 skeletal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 49 publications
(111 reference statements)
0
44
0
Order By: Relevance
“… 82 The overexpression of TRPC1 or TPRC4 enhances SOCE and accelerates the terminal differentiation of human myoblasts to myotubes. 83 Changes in the SOCE in mouse skeletal myotubes involve changes in TPRC4 expression, 84 , 85 but no mechanism has been suggested for these changes. Considering the relatively high expression of TRPC4 in skeletal muscle, more research is needed to reveal the role of TRPC4 in skeletal muscle.…”
Section: Extracellular Ca 2+ Entry Into Skeletal Mmentioning
confidence: 99%
See 2 more Smart Citations
“… 82 The overexpression of TRPC1 or TPRC4 enhances SOCE and accelerates the terminal differentiation of human myoblasts to myotubes. 83 Changes in the SOCE in mouse skeletal myotubes involve changes in TPRC4 expression, 84 , 85 but no mechanism has been suggested for these changes. Considering the relatively high expression of TRPC4 in skeletal muscle, more research is needed to reveal the role of TRPC4 in skeletal muscle.…”
Section: Extracellular Ca 2+ Entry Into Skeletal Mmentioning
confidence: 99%
“… 123 Recent reports showed that MG53 binds to Orai1 and colocalizes with Orai1 in the sarcolemmal membrane of mouse skeletal myotubes, and established that MG53–Orai1 interaction enhances SOCE along with increases in the expression levels of TRPC3, TRPC4 and calmodulin 1. 84 …”
Section: Proteins Related To Extracellular Ca 2+ Ementioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of STIM1 and/or SOCE in skeletal muscle diseases, by way of proteins such as TRPC3 and MG53, have also been reported in the literature ( 115 121 ). In addition, other possible factors that could contribute to skeletal muscle diseases have also been examined in several articles ( 54 , 122 124 ).…”
Section: Skeletal Muscle Diseases That Involve Stim1 And/or Skeletal mentioning
confidence: 70%
“…This binding attenuates sarcoplasmic reticulum Ca 21 -ATPase 1a activity and subsequently causes muscle stiffness and delayed relaxation (Lee et al, 2012). MG53 has also been found to regulate extracellular Ca 21 entry via Orai1 and intracellular Ca 21 release through Ry receptor 1 during skeletal muscle contraction (Ahn et al, 2016); however, the role of MG53 in muscle electrophysiology merits further study.…”
Section: Mg53 In Skeletal Musclementioning
confidence: 99%